Oral and Written Gospel: A Critique of Werner Kelber - Halverson, John (New Testament studies, 1994)
In The Oral and Written Gospel, Werner Kelber argues that the first written gospel was an attempt to supersede oral tradition by the creation of a literary ‘counterform’. It aimed to discredit ‘oral authorities’ (identified as the disciples and family of Jesus and Christian prophets). Similarly, the paucity of sayings in Mark indicates a suspicion of the sayings genre, which is taken to be the oral genre par excellence. The sayings represent the living voice of the living Lord. The substitution of a written gospel would silence that voice as an ongoing phenomenon by relegating it to the dead past. The passion narrative is essentially the creation of Mark, and with its emphasis on the death and post-resurrectional silence of Jesus, creates a new Christology in opposition to the ‘oral Christology’ of the sayings, which never refer to the death of Jesus. The net effect of the written gospel was to inaugurate a theology (or ‘hermeneutic’) of death and absence in contradiction to the principle of presence that informed the oral tradition.